Corporate Social Responsibility Disclosure by Sudanese Listed Commercial Banks - Abdelnur, Obeid Ahmed Obeid (International Review of Management and Marketing, 2021)
The purpose of this study is to investigate the extent of Corporate Social Responsibility (CSR) disclosure in the annual reports of Sudanese commercial banks listed on the Khartoum Stock Exchange (KSE). The paper uses content analysis method by reviewing 61 annual reports of 10 listed banks over a period of 7 years. Content analysis used to analyze the size and methods of CSR disclosure in published annual reports, beside the areas of social responsibility that are disclosed. The study found that all banks covered by the study disclosed information regarding CSR in their annual reports. In terms of disclosure methods, the results showed that the banks used all methods (financial, quantitative and descriptive) to disclose social responsibility information, considering that most of the information contained in the annual reports was in a descriptive form. The study revealed that most banks disclosed information related to human resources and product and consumer, then community involvement, followed by disclosure of environmental issues. This research paper provides new evidence for the literature in this area and may encourage comparative studies on CSR studies from different perspective Keywords: Corporate social responsibility, Sudan, disclosure, annual reports, commercial banks. JEL Classification: M140 DOI: https://doi.org/10.32479/irmm.11097